Textbook Analysis of English Learning Materials in Enhancing Students’ Reading Comprehension at Secondary School Level - Naufal Budiman; Azana Rahma; Putri Rizky Ramadhani; Lia Nur Amaliah; Mulida Isfandiawaty; Elyza Martiarini (International Journal of Technology and Education Research, 2026)
Reading comprehension is an essential skill in English learning at the secondary school level because it supports students' ability to understand, analyze, and evaluate information contained in texts. Textbooks, as the primary learning resource, play a crucial role in shaping the quality of reading learning. This study aims to analyze English learning materials in textbooks and their contribution to the development of secondary school students' reading comprehension skills. This study used a qualitative approach with a literature study method through content analysis of relevant scientific articles published in the 2021–2025 period. The results showed that the reading materials in textbooks generally met curriculum requirements, had an adequate level of readability, and provided a variety of text types and exercises that supported the development of basic reading skills, such as identifying main ideas, understanding vocabulary, and finding detailed information. The main findings of this study revealed that most reading activities still focused on literal comprehension, so the development of inferential, evaluative, and critical thinking skills was not optimally accommodated. Some reading materials were still not contextualized to students' experiences and environments. This study contributes by identifying the strengths and weaknesses of reading materials in English textbooks and emphasizes the importance of integrating Higher Order Thinking Skills (HOTS)-based activities, the use of authentic texts, and more relevant contexts to improve the quality of reading instruction in secondary schools. These findings can serve as a reference for teachers, textbook developers, and curriculum designers in developing more effective reading instructional materials that meet the demands of 21st-century learning.